Pengaruh Kompensasi dan Kepemimpinan Transformasional Terhadap Kepuasan Kerja dimediasi oleh Motivasi Kerja - Umar Yeni Suyanto; Ika Purwanti; Muhammad Dzikri Abadi; Agung Hirmantono; Mokhtar Sayyid (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
This research aimed to examine and to analyze the effect of compensation and transformational leadership on job satisfaction, either directly or indirectly, mediated with job motivation variable in Muhammadiyah Hospital of Lamongan (thereafter called RSML). This study was an explanatory research; the analysis method employed was Partial Least Square (PLS). The population of research consisted of 364 employees of Muhammadiyah Hospital of Lamongan, while the sample consisted of 79 employees, taken using Slovin technique. The results showed that compensation and transformational leadership are fundamental instruments underlying Muhammadiyah Hospital of Lamongan in improving its employees’ job motivation and satisfaction.